Usefulness of Quantitative Susceptibility Mapping for the Diagnosis of Parkinson Disease - Murakami, Y.; Kakeda, S.; Watanabe, K.; Ueda, I.; Ogasawara, A.; Moriya, J.; Ide, S.; Futatsuya, K.; Sato, T.; Okada, K.; Uozumi, T.; Tsuji, S.; et al. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Quantitative susceptibility mapping allows overcoming several nonlocal restrictions of susceptibility-weighted and phase imaging and enables quantification of magnetic susceptibility. We compared the diagnostic accuracy of quantitative susceptibility mapping and R2* (1/T2*) mapping to discriminate between patients with Parkinson disease and controls.MATERIALS AND METHODS: For 21 patients with Parkinson disease and 21 age- and sex-matched controls, 2 radiologists measured the quantitative susceptibility mapping values and R2* values in 6 brain structures (the thalamus, putamen, caudate nucleus, pallidum, substantia nigra, and red nucleus).RESULTS: The quantitative susceptibility mapping values and R2* values of the substantia nigra were significantly higher in patients with Parkinson disease (P < .01); measurements in other brain regions did not differ significantly between patients and controls. For the discrimination of patients with Parkinson disease from controls, receiver operating characteristic analysis suggested that the optimal cutoff values for the substantia nigra, based on the Youden Index, were >0.210 for quantitative susceptibility mapping and >28.8 for R2*. The sensitivity, specificity, and accuracy of quantitative susceptibility mapping were 90% (19 of 21), 86% (18 of 21), and 88% (37 of 42), respectively; for R2* mapping, they were 81% (17 of 21), 52% (11 of 21), and 67% (28 of 42). Pair-wise comparisons showed that the areas under the receiver operating characteristic curves were significantly larger for quantitative susceptibility mapping than for R2* mapping (0.91 versus 0.69, P < .05).CONCLUSIONS: Quantitative susceptibility mapping showed higher diagnostic performance than R2* mapping for the discrimination between patients with Parkinson disease and controls.Azarea under the receiver operating characteristic curvePDParkinson diseaseQSMquantitative susceptibility mappingROCreceiver operating characteristic